Implementasi IMC Model Dwi Sapta pada Merci Cafe dalam Industri Coffee Shop yang Kompetitif - Chilyatun Nisa Alifiul Anfi; Augustin Mustika Chairil (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Implementation of Integrated Marketing Communication (IMC) Dwi Sapta Model is applied by Merci Café in facing the increasingly competitive coffee shop industry, especially in the Sidoarjo area. IMC Model Dwi Sapta is an integrated marketing communication approach designed to deliver messages consistently through various communication channels. This model consists of three main stages, namely Discovery Circle, Intent Circle, and Strategy Circle. At the Discovery Circle stage, Merci Café uses analysis of the market, coffee consumption trends, and consumer behavior, with the aim of understanding the brand's position in the local market. Then at the Intent Circle stage focuses on identifying problems and brand advantages, which includes analyzing internal and external factors in influencing business performance. Furthermore, at the Strategy Circle stage, Merci Café designed a communication strategy by utilizing various channels, including advertising, events and experiences, public relations and publicity, word of mouth, and social media. This strategy is designed to increase awareness, strengthen customer loyalty, and create a unique experience for consumers so as to strengthen Merci Café's position in the competitive coffee shop industry. The research method used is descriptive qualitative with data collection techniques in the form of in-depth interviews, observation, and documentation analysis. The results showed that the implementation of the IMC Dwi Sapta Model can help Merci Café in strengthening its brand position in the market by using local trends and delivering effective messages to target audiences through effective communication strategies.